Progresos en el control de la hemorragia posparto: una revisión semisistemática. - Briones Garduño, Jesús Carlos (Ginecología y Obstetricia de México)
BACKGROUND: Postpartum hemorrhage remains a leading cause of maternal mortality worldwide. In Mexico, postpartum hemorrhage was the leading cause of direct maternal death in 2023. OBJECTIVE: To review the medical care of patients with postpartum hemorrhage and new technologies such as the JADA system. METHODOLOGY: A semi-systematic review that included articles in English and Spanish of the type of controlled clinical trials, cohort and observational studies with a publication date in the last 11 years (2014 to 2024). The reference search was limited to the PubMed-Medline database, with the search strategy defined by the keywords (MeSH): "hemorrhage/prevention & control", "hemorrhage/therapy". RESULTS: 1083 articles were identified. In the first stage of the selection process (title and abstract), 300 articles were retained. In the second phase (full text), 35 were selected and the rest were rejected for not being directly related to postpartum hemorrhage, duplicate articles, studies with weak methodology, or not relevant. CONCLUSIONS: The choice of treatment depends on the severity and cause of the bleeding, the patient's response to initial general treatment, and the availability of resources and specialized medical equipment. It may include a combination of noninvasive or invasive measures, ranging from homeostatic treatment to surgical intervention. Evidence has shown that the intrauterine vacuum-controlled hemorrhage device has the potential to be used early to rapidly and effectively control postpartum hemorrhage.